Correction: Design and chemoproteomic functional characterization of a chemical probe targeted to bromodomains of BET family proteins. Issue 1 (8th December 2014) - Wu, Jiang; Shin, Julia; Williams, Cara M. M.; Geoghegan, Kieran F.; Wright, Stephen W.; Limburg, David C.; Sahasrabudhe, Parag; Bonin, Paul D.; Lefker, Bruce A.; Ramsey, Simeon J.
Abstract : Correction for 'Design and chemoproteomic functional characterization of a chemical probe targeted to bromodomains of BET family proteins' by Jiang Wu et al., Med. Chem. Commun., 2014, 5, 1871–1878.